2008
DOI: 10.1056/nejmoa070447
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Disuse Atrophy of Diaphragm Fibers in Mechanically Ventilated Humans

Abstract: The combination of 18 to 69 hours of complete diaphragmatic inactivity and mechanical ventilation results in marked atrophy of human diaphragm myofibers. These findings are consistent with increased diaphragmatic proteolysis during inactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
907
4
64

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,303 publications
(1,051 citation statements)
references
References 27 publications
33
907
4
64
Order By: Relevance
“…While animal studies consistently indicated that prolonged MV promotes VIDD, the question of whether long-term ventilator support produces VIDD in humans remained unknown until a milestone study published in 2008 revealed that prolonged MV results in rapid diaphragmatic atrophy in humans (58). These seminal findings have now been confirmed by other groups, and together, these studies clearly demonstrate that prolonged MV results in the rapid development of both diaphragmatic atrophy and contractile dysfunction in humans (39,42,47).…”
Section: Ventilator-induced Diaphragm Dysfunction: Historical Overviewsupporting
confidence: 71%
See 1 more Smart Citation
“…While animal studies consistently indicated that prolonged MV promotes VIDD, the question of whether long-term ventilator support produces VIDD in humans remained unknown until a milestone study published in 2008 revealed that prolonged MV results in rapid diaphragmatic atrophy in humans (58). These seminal findings have now been confirmed by other groups, and together, these studies clearly demonstrate that prolonged MV results in the rapid development of both diaphragmatic atrophy and contractile dysfunction in humans (39,42,47).…”
Section: Ventilator-induced Diaphragm Dysfunction: Historical Overviewsupporting
confidence: 71%
“…To date, three independent studies have evaluated the impact of prolonged MV on diaphragmatic atrophy in humans. The first report demonstrated that 18 -69 h of full support MV results in significant diaphragmatic atrophy (ϳ50% reduction in fiber cross sectional area) of both type I (slow) and type II (fast) muscle fibers in the costal diaphragm (58). This original finding was recently confirmed in another study indicating that diaphragmatic fiber atrophy occurs in humans exposed to full support MV for Ն24 h with the magnitude of the diaphragmatic atrophy being significantly correlated with the duration of MV (47).…”
Section: Mv-induced Diaphragm Atrophymentioning
confidence: 99%
“…In a previous study, diaphragm dysfunction in ICU‐AW patients was observed in 80% of patients, and 50% had a failed extubation and died during the ICU stay 6. A range of 18‐69 hours of complete diaphragmatic inactivity and MV support results in marked diaphragm myofiber atrophy 7. In our patient, the diaphragm dysfunction might be due to ICU‐AW, which in turn led to extubation failure.…”
Section: Discussionsupporting
confidence: 53%
“…Kann die geschonte und bereits atrophierte Atemmuskulatur [6] am Beatmungsgerät wieder trainiert und gleichzeitig die Belastungsgrenze der Atempumpe so frühzeitig erkannt werden, dass es nicht zu einer Erschöpfung der Atemmuskeln kommt? Aus den großen Studien Mitte der 1990er Jahre wissen wir, dass ein respiratorunterstützter Weaning-Modus, näm-lich der "Synchronized-intermittentmandatory-ventilation"(SIMV)-Modus, einem simplen T-Stück-Versuch oder der einfachen Druckunterstützung ("pressure support ventilation", PSV) bezüglich der erfolgreichen Entwöhnung unterlegen war [5].…”
Section: Die Entwöhnung Oder Das Weaning Beginnt Mit Der Intubationunclassified